Learning Styles and Teaching Methods for Dental Students of Tehran Islamic Azad University of Medical Sciences in 2018 - Romina Abrishambaf; Fatemeh Shahsavari; Maryam Jolehar (Mashhad University of Medical Sciences, 2022)
Introduction: Students show considerable differences in their learning styles and abilities to use information; this matter plays a significant role in how to teach them. In view of that, reflecting on various learning styles among students and accommodating them to meet the requirements of teaching practices can contribute to learning at higher levels along with fulfilling more academic achievements. Therefore, the present study investigated learning styles among dental students at the Islamic Azad University, Tehran, Iran.Materials and Methods: This study was a descriptive cross-sectional research, in which the VARK Questionnaire consisting of four learning styles (i.e., visual, aural, read/write, and kinesthetic) was utilized. The questionnaire contained 16 statements/items with four options representing a learning style. After determining the dominant learning style in students, the role of related factors was determined using regression analysis.Results: Among the 442 participants in this study, 248 (56.1%) and 194 (43.9%) individuals were female and male, respectively. Data analysis revealed that a large proportion of the students (98%) were tapping one of the mentioned learning styles. The most and least frequent styles were found to be the aural (32.98%) and visual (19%) types, respectively.Conclusion: It was concluded that most dental students were keeping to the aural learning style. In this regard, it seems that focusing on teaching strategies that reinforce learning styles, especially the aural type, can significantly help to improve learning processes and fulfill academic achievements among university students.